Accuracy of doppler ultrasonography in the evaluation of hemodialysis arteriovenous fistula maturity - João Humberto da Fonseca Junior; Guilherme Benjamin Brandão Pitta; Fausto Miranda Júnior (Revista do Colégio Brasileiro de Cirurgiões)
OBJECTIVE: to determine the accuracy of Doppler ultrasonography (USD) for hemodialysis arteriovenous fistula (AVF) maturity. METHODS: we included patients with no prior AVF. Each patient underwent two USD examinations. After initiation of hemodialysis, we followed the patients during the first month of the access use and verified its adequacy to hemodialysis sessions. At statistical analysis we measured specificity, sensitivity, accuracy, ROC curve (Receiver operator characteristic) curve, TG-ROC (Two graph - receiver operator characteristic) and logistic regression. RESULTS: we included 76 patients, of which 51 completed the study. They formed two groups, those who have had good adequacy for hemodialysis (45) and those who had not (6). The average flow volume (FV) and the average draining vein diameter (DVD) of each group were, respectively: 940mL/min (95% CI: 829-1052) and 325mL/min (95% CI: 140-510); and 0.48cm (95% CI: 0.45-0.52) and 0.33cm (95% CI: 0.27-0.40). The area under the ROC curve of FV and DVD were 0.926 and 0.766, respectively. CONCLUSION: the accuracy of the measured volume flow measured at the draining vein to evaluate maturation of hemodialysis arteriovenous fistula was 85%.